2003
DOI: 10.1007/bf03194261
|View full text |Cite
|
Sign up to set email alerts
|

Cranial ontogeny ofLutreolina crassicaudata (Didelphidae): a comparison withDidelphis albiventris

Abstract: 2003. Cranial ontogeny of Lutreolina crassicaudata (Didelphidae): a comparison with Didelphis albiventris. Acta Theriologica 48: 1-9.Metatherians experience the greatest developmental changes during extrauterine life. Following previous studies on Didelphis albiventris Lund, 1840, we examined the postweaning cranial allometry of size of the Neotropical marsupial Lutreolina crassicaudata (Desmerest, 1804). Our aim was to compare growth patterns of both species to identify traits particular to each species and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 10 publications
4
50
1
4
Order By: Relevance
“…Qualitative and allometric analyses of growth allowed us to explore how distinctive the skull development of D. gliroides is in a context of comparative ontogeny. On the basis of our previous work on large-sized didelphids (Abdala et al, 2001;Flores et al, 2003), we show that the overall pattern of skull growth in D. gliroides is highly conservative. In turn, we contend that a minority of the observed developmental trends may be uniquely derived, but this remains to be contrasted with yet unknown ontogenetic patterns of small-sized didelphids and australidelphians.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Qualitative and allometric analyses of growth allowed us to explore how distinctive the skull development of D. gliroides is in a context of comparative ontogeny. On the basis of our previous work on large-sized didelphids (Abdala et al, 2001;Flores et al, 2003), we show that the overall pattern of skull growth in D. gliroides is highly conservative. In turn, we contend that a minority of the observed developmental trends may be uniquely derived, but this remains to be contrasted with yet unknown ontogenetic patterns of small-sized didelphids and australidelphians.…”
Section: Introductionmentioning
confidence: 57%
“…C and G). Abdala et al (2001) and Flores et al (2003) observed these changes in two didelphids and proposed that the adjustment of the jaw articulation through the expansion of the condyle facilitates the safety of the mandibular movements during strenuous bites. A functionally related change is the development of the masseteric line in adults, for insertion of the deep masseter muscle (based on Didelphis marsupialis; Turnbull, 1970).…”
Section: Qualitative Trendsmentioning
confidence: 97%
“…The nascent literature on didelphid cranial morphometrics is not large, but it includes studies of intraspecific ontogenetic variation (Abdala et al, 2001;Flores et al, 2003), multivariate comparisons of conspecific species (e.g., Ventura et al, 1998Ventura et al, , 2002Cerqueira and Lemos, 2000), analyses of evolutionary rates (Lemos et al, 2001), geometric modeling of taxonomic variation (Astú a de Moraes et al, 2000), and preliminary attempts to explain shape differences in functional terms (e.g., Medellín, 1991).…”
Section: Cranium and Mandiblementioning
confidence: 99%
“…Like other didelphid marsupials (Gardner, 1973;Abdala et al, 2001;Flores et al, 2003), young mouse opossums are weaned long before they are morphologically mature, with the result that mixed-age series of conspecific individuals often include specimens that differ conspicuously in size and size-correlated (allometric) proportions. Because immature (juvenile and subadult) individuals seldom exhibit all the diagnostic traits that allow confident taxonomic identifications of adults, careful attention to dental indicators of morphological maturity is important.…”
Section: Ontogenetic Variation and Sexual Dimorphismmentioning
confidence: 99%